2022
DOI: 10.1111/exd.14528
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis of nail microbiome in patients with psoriasis

Abstract: Shifts in skin microbiome are considered to be involved in the pathogenesis of psoriasis. However, data on the microbial dysbiosis of nail psoriasis are scarce. In this study, we aim to investigate and characterize the nail bacterial and fungal microbiome in patients with psoriasis. Nail samples were collected prospectively from 36 subjects with nail psoriasis, 24 psoriatic subjects without nail involvement and 32 healthy controls. Amplicon sequencing was performed to evaluate the bacterial and fungal communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Recently, accumulating evidence has demonstrated that the imbalance and dysbiosis of cutaneous microbiota can result in inflammatory skin diseases, such as atopic dermatitis, acne vulgaris, and psoriasis [ 42 45 ]. Mechanistically, the skin microbiota promotes the expression of endogenous retroviruses (ERVs) and triggers the activation of skin immunity, which is cGAS-STING pathway dependent.…”
Section: The Regulatory Role Of Cgas-sting Signaling In Cutaneous Dis...mentioning
confidence: 99%
“…Recently, accumulating evidence has demonstrated that the imbalance and dysbiosis of cutaneous microbiota can result in inflammatory skin diseases, such as atopic dermatitis, acne vulgaris, and psoriasis [ 42 45 ]. Mechanistically, the skin microbiota promotes the expression of endogenous retroviruses (ERVs) and triggers the activation of skin immunity, which is cGAS-STING pathway dependent.…”
Section: The Regulatory Role Of Cgas-sting Signaling In Cutaneous Dis...mentioning
confidence: 99%
“…Candida albicans has been reported to be associated with psoriasis [132]. For instance, there is a higher rate of concomitant fungal infections in patients with nail psoriasis, and enhanced Candida colonization is associated with more severe disease states [133].…”
Section: Candidamentioning
confidence: 99%